COVID-19 and isolation: Risks and implications in the scenario of new variants - Dias, Viviane Maria de Carvalho Hessel (2022)
With the emergence of new variants of SARS-CoV-2, questions about transmissibility, vaccine efficacy, and impact on mortality are important to support decision-making in public health measures. Modifications related to transmissibility combined with the fact that much of the population has already been partially exposed to infection and/or vaccination, have stimulated recommendations to reduce the isolation period for COVID-19. However, these new guidelines have raised questions about their effectiveness in reducing contamination and minimizing impact in work environments. Therefore, a collaborative task force was developed to review the subject in a non-systematic manner, answering questions about SARS-CoV-2 variants, COVID-19 vaccines, isolation/quarantine periods, testing to end the isolation period, and the use of masks as mitigation procedures. Overall, COVID-19 vaccines are effective in preventing severe illness and death but are less effective in preventing infection in the case of the Omicron variant. Any strategy that is adopted to reduce the isolation period should take into consideration the epidemiological situation of the geographical region, individual clinical characteristics, and mask for source control. The use of tests for isolation withdrawal should be evaluated with caution, due to results depending on various conditions and may not be reliable.